Pelatihan Strategi Content Marketing untuk Meningkatkan Daya Saing UMKM di Desa Montong Gamang, Lombok Barat - Pawestri, Setyaning; Baiq Ananda Nurhaliza; Ditayara Seftiyani; Lalu Ami Osalan; Neva Ayuliani; Nurmahraini; Rafidi Nasyuro; Sandi Lorian Rubay; Saripah Aminah (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
As technology and digitalization advance, online marketing has become a crucial strategy for enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), including those in Montong Gamang Village, West Lombok, West Nusa Tenggara Province. To address this, a content marketing training session was held on January 18, 2024, aimed at equipping MSME owners with the skills to utlizie content-based marketing for promoting their handcrafted products. The training emphasized the importance of creating relevant and engaging content to build sustainable customer relationships and improve brand awareness. It also distinguished between digital marketing and content marketing, while introducing platforms like TikTok to expand market reach and drive product sales. Conducted by the Real Work Study (KKN) team from Universitas Mataram, with lecturer serving as resource person, the event fostered active participation through discussions and Q&A sessions, enhancing participants' understanding of storytelling in marketing to create better content. The training was well-received, with high enthusiasm from MSME owners, who are now eager to apply online marketing strategies. Evaluation results showed a significant improvement in their grasp of content marketing concepts. To ensure long-term success, follow-up activities are recommended, including continuous mentoring, content calendar creation, advanced digital marketing training, collaborations with influencers, and the development of e-commerce platforms. Ultimately, the training aims to positively impact the local economy and improve the quality of life in Montong Gamang Village, helping MSMEs become more competitive in the digital marketplace.